2012
DOI: 10.1073/pnas.1118759109
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cysteine-rich head domain in activation and desensitization of the P2X1 receptor

Abstract: P2X receptors (P2XRs) are ligand-gated ion channels activated by extracellular ATP. Although the crystal structure of the zebrafish P2X4R has been solved, the exact mode of ATP binding and the conformational changes governing channel opening and desensitization remain unknown. Here, we used voltage clamp fluorometry to investigate movements in the cysteine-rich head domain of the rat P2X1R (A118-I125) that projects over the proposed ATP binding site. On substitution with cysteine residues, six of these residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 24 publications
8
71
0
Order By: Relevance
“…For example, ATP binding to the cleft and subsequent cleft closure were predicted to occur based on proximity tethering (11), normal mode analysis (12), and both metal bridging and spectroscopic studies (13,14). In addition, the accessibility of both methanethiolsulfonate compounds and metals (Ag + and Cd 2+ ) to cysteine residues introduced into TM1 and TM2 (6)(7)(8) is consistent with the expansion of the external pore predicted from the zfP2X4 structures (Fig.…”
supporting
confidence: 58%
“…For example, ATP binding to the cleft and subsequent cleft closure were predicted to occur based on proximity tethering (11), normal mode analysis (12), and both metal bridging and spectroscopic studies (13,14). In addition, the accessibility of both methanethiolsulfonate compounds and metals (Ag + and Cd 2+ ) to cysteine residues introduced into TM1 and TM2 (6)(7)(8) is consistent with the expansion of the external pore predicted from the zfP2X4 structures (Fig.…”
supporting
confidence: 58%
“…Those conformational changes are distinct from previously identified allosteric events essential for channel activations, such as the downward motion of cysteine-rich head domain, tightening of the ATP-binding site jaw and the upper vestibule expansions 5,6,8,9 . As revealed by the spontaneous closure of the ATP-binding site jaw (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have demonstrated that a downward motion of the cysteine-rich head domain, tightening of the ATP-binding site jaw and upper vestibule expansion are essential for activation, desensitization and sustained activation of P2X receptors [5][6][7][8][9][10] , with data obtained from the application of multiple approaches, including electron microscopy 10 , voltage-clamp fluorometry 9 , engineering EC metal bridges 8,11 , normal mode analysis (NMA) 7 , molecular dynamics (MD) simulations 7 and fast-scanning atomic force microscopy 6 . Those studies provide new insights into the dynamics of EC domain as well as the movements of the whole receptor during channel gating.…”
mentioning
confidence: 99%
“…3), the decreased current density in those mutations might be attributed to altered channel gating. Previous studies demonstrated that the head, the DF, and the LF domains have participated in nearly every essential or constituent element of P2X channel gating (20 -22, 24, 39, 42), including channel desensitization (24). Given that the changed salt bridge possibly resulted in the conformational changes in ␤2,3 and its physically coupled head and LF domains, the decreased current density in those mutants may be attributed to the combination of the affecting factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…1F). The increased EC 50 may originate from the fact that the motion of this domain was associated with the downward movement of the head domain, which is coupled with the ATP binding and channel gating activity (20,24,42). However, compared with the mutations at positively charged residues, which interact directly with the negative triphosphate of ATP, such as K71A and K69R (the EC 50 of ATP Ͼ20 mM) (43,44), the rightward shift of the concentrationresponse curve for D85A was nearly negligible.…”
Section: Salt Bridge Between Arg-309 and Asp-85 Is Essential For Rp2xmentioning
confidence: 95%